NILAI FEMINISME KISAH PEREMPUAN DALAM AL QURAN - layyina sifa (BUANA GENDER : Jurnal Studi Gender dan Anak, 2019)
Everything about women and womenhood are always interesting to discuss either from economic, social, edocational or theological aspect. Some discourses should be discussed in order to present thoughts, theories or policies friendly to women’s right and to avoid  inequality in gender. The most interesting issue relate to theological framework. Religious text is often claimed to be one source of women discrimination and gender inequality. Some stories in religious text (al Quran) such as story of creation of Adam and Hawa and story of Maryam contain ideas that woman is a second human and that she gets subordination and injustice treatment. Actually, there are lot of researches about story of Quran (qashash al Quran), but they often stuck on the historical and chronological discussion. They forget some values behind those stories especially stories about women. Women as main figure surely has a special role to show the main value for women justice and equal right. The main cause of those discriminative interpretaion is that; most of Quranic interpreters are man, therefore, the result of interpretion is not considering women’s right. And the other cause is the use of israiliyyat stories which often blame and underestimate women’s position. Thus, we need to present new interpretaion of stories in the Quran, especially stories on women that we hope such new interpretation will give  new toughts  and policies for women justice and equal right.